Pengaruh Kebijakan Dividen, Leverage, Firm Size, Earning Volatility, Dan Growth Terhadap Volatilitas Harga Saham - Ivana Dominika, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This research has a purpose, namely to prove empirically the impact of dividend policy, leverage, firm size, earning volatility and growth on stock price volatility. This research used secondary data. This research was selected data with purposive sampling technique. This research was conducted on manufacturing companies listed in Indonesian Stock Exchange (IDX) during the year 2014 – 2017. The entire sample used in this research is 26 data from manufacturing companies. The research data is processed with E-views version 10. The result of this this research shows that dividend policy, leverage, earning volatility, and growth has no significant on stock price volatility. Firm size has a positive effect and significant on stock price volatility.